1993
DOI: 10.1093/ije/22.6.1056
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differential in All-Cause and Cardiovascular Disease Mortality

Abstract: The gender differential in mortality from all causes, cardiovascular disease (CVD), ischaemic heart disease (IHD) and stroke during the mean follow-up of 11.6 years (range 10-14) was examined among 4696 men and 5714 women aged 45-64 at entry in West of Scotland. Overall mortality was 19.4/1000 person-years of observation among men and 10.8/1000 person-years among women. A multiple logistic regression model was used to control the influence of gender, along with seven other cardiovascular risk factors simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 0 publications
2
35
1
Order By: Relevance
“…Monthly menses were tracked via postcards completed by the participants. Follow-up assessment was scheduled with a participant when she reported one of the following regarding menstruation: (1) cessation for 12 months, (2) cessation followed by hormone replacement therapy for a combined total of 12 months, or (3) The baseline data for nonsmokers, continuing smokers, and those who quit after baseline are also summarized in Table 1. There were no statistically significant group differences for weight, fasting glucose, 2-hour glucose, insulin, or systolic blood pressure.…”
Section: Methodsmentioning
confidence: 99%
“…Monthly menses were tracked via postcards completed by the participants. Follow-up assessment was scheduled with a participant when she reported one of the following regarding menstruation: (1) cessation for 12 months, (2) cessation followed by hormone replacement therapy for a combined total of 12 months, or (3) The baseline data for nonsmokers, continuing smokers, and those who quit after baseline are also summarized in Table 1. There were no statistically significant group differences for weight, fasting glucose, 2-hour glucose, insulin, or systolic blood pressure.…”
Section: Methodsmentioning
confidence: 99%
“…Second, risk factors may have differential effects for males and females. A meta-analysis showed that the impact of diabetes on CHD mortality is greater for females (Lee et al, 2000), while males show greater effects of disability, cholesterol and smoking (Janghorbani et al, 1993;Kattainen et al, 2004;Marang-van de Mheen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The few existing studies that have examined the relationship of RA with MetS primarily involved women, and indicated increased mortality from CVD among those satisfying criteria for MetS. Men with RA have more extra-articular disease and a greater overall mortality (Janghorbani et al, 1993;Jawaheer et al, 2006;Mikuls et al, 2011). In general, there is a disproportionate individual impact of MetS, CVD, and RA in men.…”
Section: Discussionmentioning
confidence: 99%
“…Most data on RA, including reports related to MetS and CVD, are comprised mainly of females. The few reports on RA in males indicate a more severe course of disease, and worse outcome (Ford et al, 2002;Janghorbani et al, 1993;Jawaheer et al, 2006;Mikuls et al, 2011). Further, elderly males more often have comorbid diseases such as diabetes mellitus and hypertension that places them at even greater risk for CVD.…”
Section: Introductionmentioning
confidence: 99%